Virtual and in vitro screening of the Nottingham Managed Chemical Compound Collection vs Mycobacterium bovis and Mycobacterium tuberculosis cell wall biosynthesis enzyme: InhA. - Lamont, Malcolm (2021)
Tuberculosis is a worldwide health concern causing 10 illion new cases and 1.4 million deaths annually. Multi-drug resistance is a further issue limiting effective treatment, with the proportion of cases in this category rising each year.